A Critical Study on The Ma’ālim As-Sunna An-Nabawiyya by Ṣāliḥ Asy-Syāmī - Ja'far Assagaf (Jurnal Living Hadis, 2020)
Asy-Syāmī intended the Ma’ālim as-Sunna an-Nabawiyya to be the fifteenth in the list of the hitherto fourteen hadith books of Muslim. It is made up more concise for the people to access it more easily—of course without deteriorating the fourteen acclaimed primary sources. Reading the book more closely, this article argues that the method asy-Syāmī uses in producing the book triggers hadith scholars to question its worthiness to join the list. I further try to do critique by employing the so-called conventional hadith science recognized widely in Muslim scholarship. I find some aspects in which asy-Syāmī is quite inconsistent in treating the hadith. He take out some parts of hadith text, miscount the total number of the hadith, and do some wrong in classifying and assessing the quality of the hadith. These all make the book unworthy to join the list of primary hadith books for Muslim. However, the book helps Muslim, especially lay Muslim, to understand closer the prophetic hadith.